Efeito de um programa de ginástica laboral na saúde, estados de ânimo e estresse diário do trabalhador - Grimaldi, Gabriela [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The practice of regular physical activity has been widely recommended in the literature, indicating an improvement of the physical and psychological activities promoted through the routine of workers. In this sense, physical activity has become of great importance in the workplace, for the prevention of injuries caused by normalizing bodily functions and staff providing relaxation and socialization, basic elements of daily life a worker. This study aimed to analyze the effects of a active break program in the routine of workers in their mood and stress, even checking the influence of physical activity on quality of life of participants. We selected 15 individuals of both genders, the restaurant staff University, UNESP - Rio Claro-SP. The activities lasted four months, two times a week, at the beginning of the workday, for 15 minutes, followed by stretching and playful activity. The evaluations were answered a week before the execution of the program and lists of mood states have been answered before and after the activity, and the end of working hours and also at the beginning and end of the days when there were no interventions. After analyzing the results, we concluded that the participants have a good index of perception of quality of life with total score of 76.6 for mental and physical health and that all assets are considered in accordance with the recommendations of 150 minutes of physical activity per week. More than 50% of them have symptoms of stress found mostly in the resistance stage, and no changes were found in the mood states when practicing active break or not. We conclude that the changing of moods can be associated with the fact that workers are already active, another reason may be due to low number of participants in the study, given other studies show that there is a change and that active break interferes positively in mood states of individuals

A prática regular de atividade física vem sendo amplamente recomendada pela literatura, indicando melhora do desempenho físico e psicológico promovidos através de atividades na rotina de trabalhadores. Nesse sentido a atividade física se tornou de grande importância no ambiente de trabalho, visando à prevenção de lesões ocasionadas, normalizando as funções corporais e proporcionando aos funcionários descontração e socialização, elementos fundamentais na vida diária de um trabalhador. O presente estudo teve como objetivo analisar os efeitos de um programa de ginástica laboral na rotina dos trabalhadores, no seu estado de ânimo e estresse, verificando ainda a influência da prática de atividade física na qualidade de vida dos participantes. Participaram do estudo 15 indivíduos, de ambos os gêneros, funcionários do Restaurante Universitário da UNESP – Rio Claro-SP. O programa durou quatro meses, 2 vezes por semana, no inicio do expediente, durante 15 minutos, acompanhadas de alongamentos e atividades lúdicas. As avaliações foram respondidas uma semana antes da execução do programa e as listas de estados de ânimo foram respondidas antes e após a atividade, e ao final do expediente de trabalho e também no inicio e final dos dias em que não houver intervenções. Após a análise dos resultados concluímos que os participantes, apresentaram um bom índice de percepção da qualidade de vida com score total de 76,6 para saúde mental e física e que todos são considerados ativos de acordo com as recomendações de 150 minutos de atividade física por semana. Mais de 50% deles apresentaram sintomas de estresse encontrados em sua maioria na fase de resistência, e não foram encontradas diferenças nas alterações dos estados de ânimo quando há prática de ginástica laboral ou não. Concluímos ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ginástica; Saude e trabalho; Exercícios físicos - Aspectos psicológicos; Stress ocupacional; Gymnastics; Exercise - Psychological aspects; Job stress